Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1111/j.1468-1293.2009.00699.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HIV status and antiretroviral therapy on blood pressure

Abstract: ObjectiveHigh blood pressure is a major risk factor for cardiovascular disease and concerns have been raised over its possible association with antiretroviral drugs. The objective of this study was to explore the associations among blood pressure, HIV status and two predefined highly active antiretroviral therapy (HAART) regimens: treatment with and without nonnucleoside reverse transcriptase inhibitors (NNRTIs) (NNRTI-and non-NNRTI-based HAART). MethodA cross-sectional survey was conducted among 612 adults at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 16 publications
(45 reference statements)
0
16
2
Order By: Relevance
“…(24) In a smaller, cross-sectional study of patients attending a sexual health clinic in London, Wilson et al found an association between NNRTI use and increased blood pressure. (25) In our study, neither HAART nor NNRTI-based HAART use at enrollment were associated with either prevalent or incident hypertension, further suggesting that HIV treatment may not, in and of itself, contribute to hypertension.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…(24) In a smaller, cross-sectional study of patients attending a sexual health clinic in London, Wilson et al found an association between NNRTI use and increased blood pressure. (25) In our study, neither HAART nor NNRTI-based HAART use at enrollment were associated with either prevalent or incident hypertension, further suggesting that HIV treatment may not, in and of itself, contribute to hypertension.…”
Section: Discussioncontrasting
confidence: 72%
“…(22, 24) Inconsistent data exist about the effect of non-nucleoside reverse transcriptase inhibitors (NNRTIs) on hypertension in HIV-infected adults. (24–25) These studies encompass patients both with and without a diagnosis of AIDS. Because of the increased mortality risk of HIV-positive patients with AIDS, it is unclear whether these patients have the same risk of developing hypertension as do other HIV-positive patients.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 573 abstracts and 17 full texts, including seven duplicate records, were excluded, leaving 39 eligible observational studies. [5][6][7][8]15,16, Thirty of these included studies were cross-sectional surveys, 5,16,[18][19][20][21][22][23][24][25][26]28,[31][32][33][34][35][36][37][39][40][41][42][44][45][46]48,49 whereas the other nine were cohort studies. A total of 44 903 HIV-infected patients (28% females) from 21 countries were included in our analyses, with significantly more study participants from high-income countries compared with low-and middle-income countries (89% versus 11%).…”
Section: Discussionmentioning
confidence: 99%
“…There is a scale up of HAART use in Uganda with about 24,735 children below 15 years on HAART by 2011 [3]. While HAART has improved and prolonged life, it has been associated with metabolic abnormalities that predispose patients to a poor quality of life [4,5] HAART is associated with lipid abnormalities (dyslipidemia) like: increase in low density lipoproteins (LDL), triglycerides (TG), cholesterol and low high density lipoproteins (HDL), [69]. These, together with chronic HIV associated inflammation and activation of the immune system, may result in damage to the arteries.…”
Section: Introductionmentioning
confidence: 99%